Violent Affinities: The Evolution of the Norte del Valle Drug Trafficking Network - Caicedo-Hurtado, María Isabel; Salazar-Trujillo, Boris; Vanegas-Muñoz, Gildardo (Sociedad y Economía, 2021)
This article recounts and explains the rise and fall of the Norte del Valle drug trafficking network during 1994-2011. It contends that centrifugal forces inherent in the volatile nature of drug trafficking groups, an affinity towards violence that united its leaders, the war against drugs, and information clashes created by the new negotiating strategy with the U.S. Justice Department led to its self-destruction and the fracturing of its structure. This article suggests that the best strategies for removing the key player function for a specific network but are not effective whatsoever for mutant networks that emerge from the remains of destroyed networks.